Cytotoxic activity of crude extracts of Dendrobium amoenum and detection of bioactive compounds by GC-MS (Botanica Orientalis: Journal of Plant Science, 2018)
Dendrobium amoenum is an epiphytic orchid used as tonic because it has many derivatives of phenols. The crude extract of this orchid has been shown to have antioxidant activity. The objectives of this research are to explore the cytotoxic activity of antioxidant-rich crude extract against the human cervical carcinoma and glioblastoma cell lines by MTT assay and to detect the compounds by GC-MS. Methanol (DAM) extract of D. amoenum showed high cell growth inhibition percentage against the tested cell lines. DAM extract showed high cytotoxic activity against HeLa cells (IC50 – 110.22 μg/ml) and least activity against U-251 cells (IC50 – 550.55 μg/ml). Thirteen compounds were detected and identified in the extract. Based on abundance, four major compounds detected were: (E)-13-docosenoic acid; oleic acid; 11-octadecenoic acid, methyl ester; and hexadecanoic acid, 2,3-dihydroxypropyl ester. The cytotoxic activity of DAM extract is probably due to the presence of these bioactive compounds, confirmation of which needs further investigation. The result also highlighted the potential of this orchid as the source of natural anticancer drug and to explore their isolation, identification and characterization.Botanica Orientalis – Journal of Plant Science (2017) 11: 38–42